2011
DOI: 10.1111/j.1399-3046.2010.01452.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rural status on health outcomes in pediatric liver transplantation: A single center analysis of 388 patients

Abstract: Rural status of patients may impact health before and after pediatric LT. We used UI codes published by the USDA to stratify patients as urban or rural depending county residence. A total of 388 patients who had LT and who met criteria were included. Rejection, PTLD, and survival were used as primary outcome measures of post-LT health. UNOS Status 1 and PELD/MELD scores >20 were used as secondary outcome measures of poorer pre-LT health. Logistic regression models were run to determine associations. We did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…66,88 However, in adjusted analyses, another study found rural patients were less likely to experience rejection but also less likely to survive at 5-year follow-up. 98 There were no significant differences in acute rejection or graft survival based on geographical remoteness in Australia and New Zealand. 59 However, remoteness of residence was the only predictor of mortality or re-transplantation among Australian children of Aboriginal and Torres Strait Islander Identity.…”
Section: Urban Versus Rural/remotenessmentioning
confidence: 83%
See 1 more Smart Citation
“…66,88 However, in adjusted analyses, another study found rural patients were less likely to experience rejection but also less likely to survive at 5-year follow-up. 98 There were no significant differences in acute rejection or graft survival based on geographical remoteness in Australia and New Zealand. 59 However, remoteness of residence was the only predictor of mortality or re-transplantation among Australian children of Aboriginal and Torres Strait Islander Identity.…”
Section: Urban Versus Rural/remotenessmentioning
confidence: 83%
“…Two studies comparing outcomes across urban or rural residences found no significant difference in adherence or graft failure risk 66,88 . However, in adjusted analyses, another study found rural patients were less likely to experience rejection but also less likely to survive at 5‐year follow‐up 98 . There were no significant differences in acute rejection or graft survival based on geographical remoteness in Australia and New Zealand 59 .…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly troubling for pediatric patients with end‐stage liver disease because the independent effect of UNOS region on waitlist survival and transplantation is likely exacerbated by the much smaller number of pediatric liver transplant centers. While a single‐center study did not find a significant association with rural areas and post‐transplant outcomes, a registry‐based study found differences only at 6 months with acute rejection . These studies underline the importance of understanding whether and how distance affects access to pediatric liver transplantation to determine whether potential targets for intervention, such as additional education, services, and support, can overcome distance barriers.…”
Section: Introductionmentioning
confidence: 93%
“…The UI code, a measure of how rural or urban a county is, was included as a covariate given published research documenting disparities in transplant-related health by proximity to metropolitan areas (Park et al, 2011). UI codes are assigned by the United States Department of Agriculture and range from 1 to 12, with one representing large metropolitan areas and 12 representing rural areas smaller than 2,500 residents not adjacent to a metropolitan area (United States Department of Agriculture, 2019).…”
Section: Urban Influence (Ui) Codementioning
confidence: 99%